Nursing management of constipation in a patient with chest stuffiness and pains treated with Traditional Chinese Medicine external treatment (中医外治法治疗1例胸痹心痛病患者便秘的护理体会) - ZHANG Yue (张悦); ZHANG Yuanyuan (张园园); LI Yuye (李玉叶); SHEN Juan (沈娟); WANG Xiongyu (王星予); TANG Ling (唐玲); E Haiyan (鄂海燕) (中西医结合护理)
This paper summarized the nursing management of constipation in a patient with Chest Stuffiness and Pains treated with Traditional Chinese Medicine (TCM) external treatment. Based on the nursing evaluation, a combination of TCM external treatment including acupoint application, auricular acupoint pressing therapy and abdominal massage were carried out to relieve the clinical symptoms. The TCM external treatment may provide new ideas for treating constipation in patients with chest stuffiness and pains, and promote its clinical practice. (本文总结中医外治法治疗1例胸痹心痛病患者便秘的护理体会。通过护理评估, 选用穴位贴敷、耳穴贴压和便秘推拿技术, 改善患者便秘的症状。中医外治法联合为治疗胸痹便秘提供了新的思路, 从而促进中医外治法的临床应用与推广。)